TRANSFORMASI GMIM DAN REKONSILIASI “Suatu Kajian Teologi – Sosiologi Terhadap Penyelenggaraan Pelayanan GMIM Selaku institusi.” - Sarimbangun, Ramli (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
Transformation is a change that has taken place totally in this case, both in terms of essence and form. Reformation is a reneval to restore it to its original position. True transformation is change. Transformation is not the same as modivication, because modification only changes the surface, but not the contents. Transformation is dynamic and depends on the vision and mission of an institution, such as the Evangelical Christian Church in Minahasa (GMIM) as the context. Although etymologically the transformation and reformation are very different, but both of them influence each other. Transformation does not occur without reform. Transformation moves forward and dumps its original essence, depending on the context. The Evangelical Christian Church in Minahasa (GMIM) has stepped up. The highest synod assembly has taken ecclesiological decision to change ecclesiology. Ecclesiologicsl transformationis as institutional awareness of the institution concerning his calling assignments in this world. The impact that occurred after the 78th special synod assembly session, doted 17 to 18 – May – 2016 at walene Tou Tondano, was seen as a motivating force to continue to rise up to carry out the task of calling the church whitch belongs to God. The Evangelical Christian Church in Minahasa is a church that has a vision from God and a mission that is driven by the power of the holy Spirit, it must be flexible but firm in its stance to realize the task of calling the church. The Church will not disband and die with various waves of criticism an dissatisfaction as a result of an ecclesiastical decision, but will instead continue to be strong and grow. The Evangelical Christian Church in Minahasa is no longer local but has changed to National and Global.